Age‐associated changes of islet endocrine cells and the effects of body mass index in Japanese. Issue 1 (4th August 2013) - Mizukami, Hiroki; Takahashi, Kazunori; Inaba, Wataru; Osonoi, Sho; Kamata, Kosuke; Tsuboi, Kentaro; Yagihashi, Soroku
Abstract Aims/Introduction Impaired growth and premature death of β‐cells are implicated in the progression of islet pathology in type 2 diabetes. It remains unclear, however, how aging affects islet cells, or whether the islet change in diabetes is an augmented process of aging. We studied age‐related changes of the islet structure in Japanese non‐diabetic subjects and explored the underlying mechanism of the changes. Materials and Methods A total of 115 non‐diabetic autopsy cases were subjected to morphometric analysis for volume densities of islets, β‐ and non‐β‐cells, as well as their masses. Proliferation activity identified by Ki67, and expressions of pancreatic and duodenal homeobox (PDX)‐1, cell cycle inhibitor P16, and oxidative stress marker γH2AX were also examined. Results There was a gradual and marginal decline of volume densities of islets, β‐ and non‐β‐cells with aging, while masses of these components were increased during maturation and slowly decreased after the 40s. Islet density was high in the young, but reduced after maturation. There was only a minimal influence of increased body mass index (BMI) on the increase in β‐cell mass, but not on the other variables. Ki67 positivity and PDX‐1 expressions were high in the young, but low after maturation, whereas expressions of P16 and γH2AX were elevated in the aged. Conclusions Age‐associated decline of β‐cell mass is marginal after maturation, and the reduction of β‐cell mass could be a specific process in diabetes. The impact of BMI on the islet structure is limited in Japanese with normal glucose tolerance.